Application of ERPs to Evaluation of Clothing Comfort through physiological signals - LIU Yunjuan; CHEN Dongsheng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Based on analyzing domestic and foreign literatures concerning event-related potential research, this paper analyses the theory of comfort of wearing by using ERPs. This paper makes a summary of what comfort evaluation for wearing using ERPs, Finally propose the research direction in this domain of identifying from EEG the nerve reflection related to special feeling and neurocognitive events, for the purpose of using impersonal metrics to evaluate subjective feelings of clothing comfort and then provide a new method for designing clothing to be more comfortable. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3345